Justice for edgehogs to debate - Dworkin, Ronald (2015)
This conference was dictated on November the 22nd of 2011 in the University of Buenos Aires Law School, after Ronald Dworkin was invested with the maximum distinction that the UBA grants: the Honoris Causa doctorate